2014
DOI: 10.1111/jth.12566
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of human platelet activation by surface pannexin‐1 channels

Abstract: BackgroundPannexin-1 (Panx1) forms an anion-selective channel with a permeability up to ∼1 kDa and represents a non-lytic, non-vesicular ATP release pathway in erythrocytes, leukocytes and neurons. Related connexin gap junction proteins have been reported in platelets; however, the expression and function of the pannexins remain unknown.ObjectiveTo determine the expression and function of pannexins in human plate-lets, using molecular, cellular and functional techniques.MethodsPanx1 expression in human platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 51 publications
8
77
1
Order By: Relevance
“…Pannexins are a family with three member proteins, related to gap junctions, which form channels enhancing ATP release and Ca +2 uptake that are mechanically sensitive (Taylor et al, 2015). Recent studies have shown that activation of pannexin-1 enhances platelet activation (Taylor et al, 2014). Future studies are needed to further clarify the role of pannexins, and other potential shear-sensitive channels, as to their contribution to shear-mediated platelet activation.…”
Section: Mechano-activation – Activation Of Shear-sensitive Channelsmentioning
confidence: 99%
“…Pannexins are a family with three member proteins, related to gap junctions, which form channels enhancing ATP release and Ca +2 uptake that are mechanically sensitive (Taylor et al, 2015). Recent studies have shown that activation of pannexin-1 enhances platelet activation (Taylor et al, 2014). Future studies are needed to further clarify the role of pannexins, and other potential shear-sensitive channels, as to their contribution to shear-mediated platelet activation.…”
Section: Mechano-activation – Activation Of Shear-sensitive Channelsmentioning
confidence: 99%
“…One possible explanation of these data is that [Cl − ] o is required for efficient release of ATP and/or ADP from the platelet, but we failed to observe a change in dense granule secretion (Figure 2c). Pannexin-1 has been shown to activate in response to elevation of intracellular Ca 2+ ([Ca 2+ ] i ) [20], facilitating cytosolic ATP release [14]. It has been suggested that ADP release may occur via a similar mechanism [21].…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic [10] and transcriptomic [11] analyses have since identified numerous anion channels that may be expressed by platelets. Of these, functional expressions of CLIC1 (Intracellular Cl − channel-1) [12], TMEM16F [13], and pannexin-1 [14] have been confirmed. Indicative of a hemostatic role for anion channels, CLIC1- and TMEM16F-deficient mice have associated platelet-related bleeding phenotypes [12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of Panx-1 in mice also has the effect of reducing tumor size in vivo [8]. Moreover, Panx-1 is highly expressed in human platelets, and Panx-1 channels can promote the aggregation of platelets, which is a risk factor of cancer metastasis, by enhancing Ca 2+ influx and ATP release [9]. How do these conflicts occur?…”
mentioning
confidence: 99%